Four different emissions from a Pt(Bodipy)(PEt3)2(S-Pyrene) dyad. Issue 4 (19th December 2018) - Irmler, Peter; Gogesch, Franciska S.; Larsen, Christopher B.; Wenger, Oliver S.; Winter, Rainer F.
Abstract : A bodipy-Pt-mercaptopyrene diad emits from a pyrene-to-bodipy charge-transfer, the bodipy 1 ππ* and 3 ππ* and the pyrene 3 ππ* states. Abstract : The Pt(bodipy)-(mercaptopyrene) dyadBPtSPyr shows four different emissions: intense near-infrared phosphorescence ( Φ ph up to 15%) from a charge-transfer state pyrS˙ + -Pt-BDP˙ −, additional fluorescence and phosphorescence emissions from the 1 ππ* and 3 ππ* states of the bodipy ligand at r.t., and phosphorescence from the pyrene 3 ππ* and the bodipy 3 ππ* states in a glassy matrix at 77 K.